2010
DOI: 10.1016/j.compositesa.2009.10.023
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive model of particulate-reinforced composites taking account of particle size effects and damage evolution

Abstract: This paper deals with a constitutive model of particulate-reinforced composites which can describe the evolution of debonding damage, matrix plasticity and particle size effects on deformation and damage. An incremental damage model of particulate-reinforced composites based on the Mori-Tanaka's mean field concept has been extended to consider the particle size effects by using the Nan-Clarke's simple method. The particle size effect on deformation is realized by introducing dislocation plasticity for stress-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…A model predicting tensile properties increasing with decreasing particle diameter in MMCs by Tohgo et al 16) showed CTE difference between particle and matrix has the most contribution to tensile properties, followed by "kinematic" and "isotropic" (effects of strain gradient plasticity related to geometrically necessary dislocations for heterogeneous dislocation around a particle), then Orowan stress for dislocation to pass through aligned particles.…”
Section: Introductionmentioning
confidence: 99%
“…A model predicting tensile properties increasing with decreasing particle diameter in MMCs by Tohgo et al 16) showed CTE difference between particle and matrix has the most contribution to tensile properties, followed by "kinematic" and "isotropic" (effects of strain gradient plasticity related to geometrically necessary dislocations for heterogeneous dislocation around a particle), then Orowan stress for dislocation to pass through aligned particles.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of strengthening mechanisms in particle or fiber reinforced composites to the overall mechanical response have been analyzed by many approaches (Aghababaei and Joshi, 2013;Dai et al, 2001;Hashin, 1991;Ma et al, 2004;Shao et al, 2011;Tohgo et al, 2010;Willoughby et al, 2012). In addition, the combination of linear comparison composite with secant modulus is also broadly employed (Barai and Weng, 2011b;Weng, 1990;Zhu and Lu, 2012).…”
Section: Micromechanical Three-phase Composite Modelmentioning
confidence: 99%
“…Damage evolution in the PFC due to particle debonding requires continuous update of stiffness of composite by monitoring and prediction of the state of bonding between particle and matrix which is conveyed through some phenomenological characterization of particle debonding (Dai and Huang, 2001). Progressive debonding damage generally imposed by transformation of some percent of perfectly bonded particles to debonded particles through some averaged stress and strain criterion (Tohgo and Weng, 1994;Chen et al, 2003) or critical energy criterion (Tohgo et al, 2010;Chen et al, 2010). Though particle debonding is implicitly implemented and actual stress fields around and inside the fillers remain as unknown, micromechanical homogenization models are very powerful tools that can be used both for material modeling of PFCs and prediction of effective material properties of PFCs.…”
Section: Introductionmentioning
confidence: 99%